2020
DOI: 10.1021/jacs.9b13753
|View full text |Cite
|
Sign up to set email alerts
|

Picolinate-Directed Arene meta-C–H Amination via FeCl3 Catalysis

Abstract: Direct C–H functionalization of aromatic compounds is a powerful tool for organic synthesis; however, differentiation among the ubiquitous and often chemically similar C–H bonds remains a significant challenge. Conflation with coordinating or directing groups incorporated into the intended substrate has helped address these limitations, although access to remote sites remains limited. Herein, we report an operationally simple and sustainable direct meta-selective H2N amination of benzylic and related aromatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 42 publications
1
27
0
Order By: Relevance
“…Although C–H functionalization has emerged as a promising strategy that maximizes atom- and step-economy, state-of-the-art methods for amine synthesis typically provide N -protected or N -substituted products that require additional manipulation to access the corresponding primary amines . Recently, a few methods have been developed for primary amination of C­(sp 2 )–H bonds, including photo­redox catalysis, electro­chemical catalysis, and the use of other novel amination reagents and metal catalysts . Primary amination of C­(sp 3 )–H bonds, however, has remained elusive.…”
mentioning
confidence: 99%
“…Although C–H functionalization has emerged as a promising strategy that maximizes atom- and step-economy, state-of-the-art methods for amine synthesis typically provide N -protected or N -substituted products that require additional manipulation to access the corresponding primary amines . Recently, a few methods have been developed for primary amination of C­(sp 2 )–H bonds, including photo­redox catalysis, electro­chemical catalysis, and the use of other novel amination reagents and metal catalysts . Primary amination of C­(sp 3 )–H bonds, however, has remained elusive.…”
mentioning
confidence: 99%
“…[41][42][43][44][45][46][47][48][49][50][51][52][53] Recently, we discovered dioxazolones can undergo intermolecular N-N coupling with arylamines to make hydrazides under either iridium or iron catalysis. [54][55][56][57][58][59][60][61][62][63][64] Mechanistic studies of the Ir-catalyzed system indicated an outer-sphere nucleophilic attack of the nitrogen group of Ir-nitrenoid intermediate by amine leads to the N-N coupling product.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, while representing the advances of DGs, Anugu et al has provided a simple yet powerful strategy for meta-CÀ H amination of arenes in the presence of picolinate as a key DG (Scheme 34). [141] They have utilized this sustainable, cost-effective, and operationally easy methodology to late-stage transforms for many polyfunctional molecules involving FeCl 3 and HOSA (hydroxylamine-Osulfonic acid) in the presence of triethylamine.…”
Section: Meta-cà H Amination Through Picolinate As a Vital Directing mentioning
confidence: 99%